Implementation of Interactive Storytelling Method in Improving Learning Outcomes of Asmaul Husana Material for Students at Miftahul Jannah Langkat Private Elementary Madrasah - Yulidar; Nengsih, Yusma; Zahra; Yusuf; Yusri (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve the learning outcomes of grade 4 students at Miftahul Jannah Langkat Private Elementary School on the Asmaul Husna material using the interactive storytelling method. This method was chosen because it is considered more interesting and can help students understand the meaning and spiritual values ​​of Asmaul Husna in a more enjoyable way. This research was conducted in the form of Classroom Action Research (CAR) consisting of two cycles. Each cycle includes four stages, namely planning, implementation, observation, and reflection. Data were collected through observation of student activities, field notes, and learning outcome tests. The results showed that the interactive storytelling method succeeded in improving student understanding and learning outcomes. In the first cycle, the percentage of student learning completion reached 65%, and in the second cycle it increased to 85%. In addition, students looked more enthusiastic, active, and involved in the learning process. They found it easier to grasp the meaning of each Asmaul Husna taught because this method made learning feel more alive and interactive. Thus, the interactive storytelling method has proven to be effective not only in improving learning outcomes, but also in creating a more enjoyable and meaningful learning atmosphere for students